Reporting a Rare Case of Pleomorphic Adenoma of the Breast - Tahere Khamechian; Javad Alizargar; Tahere Mazoochi (Case Reports in Medicine)
Pleomorphic adenoma (PA) is the most common tumor type in the salivary gland. PA is uncommon in the breast tissue. Only 73 cases of PA of the breast have been reported in the world literature. We are reporting the 74th case of PA of the breast. A 61-year-old woman was referred to Shahid Beheshti Hospital Obstetric Clinic with bloody painless discharge from the right nipple. A bean size mass was detected immediately below the right nipple. After an excisional biopsy, the pathologist found proliferation in epithelial and myoepithelial cells that had small and multiple nuclei, myxoid and chondroid stroma. Immunohistochemistry stain was positive for S-100 and patchy for GFAP in tumor cells and for SMA around the tubule-glandular and tumor cell aggregates and suggested PA of the breast. It is essential for the pathologists to consider PA of the breast as a differential diagnosis of a rounded circumscribed mass in the juxta-areolar areas. Careful paraffin sections should be performed to avoid an unnecessary mastectomy.